Acute Pain Control Challenges with Buprenorphine/Naloxone Therapy in a Patient with Compartment Syndrome Secondary to McArdle's Disease: A Case Report and Review. Issue 8 (3rd May 2013) - McCormick, Zachary; Chu, Samuel K.; Chang‐Chien, George C.; Joseph, Petra
Abstract Objective We report the first case of non‐iatrogentic exertional rhabdomyolysis leading to acute compartment syndrome in a patient with McArdle's disease. We describe considerations of concurrent buprenorphine/naloxone therapy during episodes of severe acute pain. Design Case report. Case Presentation A 50‐year‐old male with a history of McArdle's disease, taking buprenorphine/naloxone for chronic pain and opioid dependence, presented to the Emergency Department with severe bilateral anterior thigh pain. Over the following 8 hours, he was given a total of 12 mg of intravenous hydromorphone with minimal pain relief. The decision was made to initiate patient‐controlled analgesia (PCA) with hydromorphone started at 0.5 mg as needed with a 15‐minute lockout. Subsequently, the patient's anterior thighs were found to be extremely tense. His creatine kinase level rose to 198, 688 units/L and compartment pressures were greater than 90 mm Hg bilaterally. The patient was taken for emergent bilateral fasciotomies. The hydromorphone PCA was increased to 0.8 mg as needed with a 15‐minute lockout and a basal rate of 0.5 mg/h. The patient's reported pain plateaued at 3/10 intensity 2 days after surgery, and he was transitioned to oxycodone and hydrocodone/acetaminophen. He followed up with his pain management physician 2 months later who restarted suboxone and a buphrenorphine transdermal patch. Discussion Buprenorphine/naloxone is being prescribed off‐label with increasing frequency for pain management in patients with or without a history of opioid abuse. Severe acute pain is more difficult to control with opioid analgesics in patients taking buprenorphine/naloxone, requiring higher than usual doses. If buprenorphine/naloxone is discontinued to better treat acute pain with other opioids, monitoring for overdose must take place for at least 72 hours.